New observational project for revealing natural and anthropogenicthreats at the near-Earth space - Harutyunian, H.; Nikoghosyan, E.; Melikian, N. D.; Azatyan, N.; Abrahamyan, H.; Paronyan, G.; Andreassian, H.; Ohanian, G.; Gevorgyan, M.; Mickaelyan, G.; Andreasyan, D.; Grigoryan, A.
Byurakan astrophysical observatory. This project initiated for revealing natural and artificial objects at the near-Earth space. This is a kind of continuation of earlier observational projects implemented at the observatory prior the collapse of Soviet Union. This time, near-Earth space monitoring is carried out at the request of the Russian agency ROSKOSMOS. For observations, the EOP-1 module is used, which includes small telescopes with a mirror diameter of 40cm, 25cm and 19cm.
Keywords: Cosmology